A study of stormwater runoff quantity and quality monitoring in UMP Gambang - Amirul Hakim, Yusrizal (2018)
Stormwater runoff is a leading contributor to pollution in streams, rivers, and lakes in nationwide. Thus stormwater runoff contains pollutants from many different sources, therefore decreasing pollution from stormwater runoff is a challenging task. It requires cooperation from residents, businesses, and municipalities. An important step in protecting streams from stormwater pollution is understanding watershed processes, stormwater characteristics, and their combined effects on streams and water quality. The objective of the study was analysis relationship between rainfall characteristic and Total Suspended Solid (TSS) at UMP Gambang. The data was collected in December 2017 until March 2018.The Portable Water Sample used to collect sample of Total Suspended Solid (TSS), meanwhile equipment Rain Gauge was collected rainfall depth. The sample are taken to environmental laboratory for Total Suspended Solid experiment. The result in December has an event, January has five events and in February has two events. The stormwater runoff relationship between rainfall depth and TSS can be taken as the longer period of rainless before rain, the higher value of Total Suspended Solid (TSS) during rain.